1994
DOI: 10.1016/0370-2693(94)01265-2
|View full text |Cite
|
Sign up to set email alerts
|

Regge gravity on general triangulations

Abstract: We investigate quantum gravity in four dimensions using the Regge approach on triangulations of the four-torus with general, non-regular incidence matrices. We find that the simplicial lattice tends to develop spikes for vertices with low coordination numbers even for vanishing gravitational coupling. Different to the regular, hypercubic lattices almost exclusively used in previous studies, we find now that the observables depend on the measure. Computations with nonvanishing gravitational coupling still revea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…The same authors studied the inclusion of the higher-derivative term (15) in [36]. On the regular lattice, their findings for R(k, a) confirmed those by Hamber, apart from the fact that they found stable expectation values even for positive R. Inserting irregular vertices pushes R to larger values and leads again to the appearance of an additional transition point.…”
Section: Non-hypercubic Latticessupporting
confidence: 59%
See 2 more Smart Citations
“…The same authors studied the inclusion of the higher-derivative term (15) in [36]. On the regular lattice, their findings for R(k, a) confirmed those by Hamber, apart from the fact that they found stable expectation values even for positive R. Inserting irregular vertices pushes R to larger values and leads again to the appearance of an additional transition point.…”
Section: Non-hypercubic Latticessupporting
confidence: 59%
“…Simulations on lattices with irregular link geometry (still with T 4 -topology) have been performed by Beirl et al [31,36]. They were obtained by adding a few vertices of low coordination number to otherwise regular lattices.…”
Section: Non-hypercubic Latticesmentioning
confidence: 99%
See 1 more Smart Citation
“…͑A brief numerical study of a kagome Ising model with three-spin interactions can be found in Ref. 13.͒ In the same manner in which we proceeded in Sec. III A, we can integrate out the a-spins to form an effective model for the b-spins.…”
Section: ͑23͒mentioning
confidence: 90%
“…for a generic large surface of volume V 4 and no accidental symmetry factors there will be V 4 such manifolds for each closed manifold since the boundary can be placed at any of the V 4 four-simplexes. If we assume that the canonical partition function is given by (36), we get: (40) which has the obvious interpretation that the probability of having a branching to a minbu of volume V 4 per unit volume is V 2 4 (1 V 4 =N 4 ) 2 . As shown in 34,19] \minbu counting" is a very convenient tool for measuring if is not too negative, both in two-dimensional and four-dimensional simplicial quantum gravity.…”
Section: Scaling Relationsmentioning
confidence: 99%